Phospholipases A in Trypanosomatids. (2nd March 2011) - Belaunzarán, María Laura; Lammel, Estela María; de Isola, Elvira Luisa Durante
Abstract : Phospholipases are a complex and important group of enzymes widespread in nature, that play crucial roles in diverse biochemical processes and are classified as A1, A2, C, and D. Phospholipases A1 and A2 activities have been linked to pathogenesis in various microorganisms, and particularly in pathogenic protozoa they have been implicated in cell invasion. Kinetoplastids are a group of flagellated protozoa, including extra- and intracellular parasites that cause severe disease in humans and animals. In the present paper, we will mainly focus on the three most important kinetoplastid human pathogens, Trypanosoma brucei, Trypanosoma cruzi, and Leishmania spp., giving a perspective of the research done up to now regarding biochemical, biological, and molecular characteristics of Phospholipases A1 and A2 and their contribution to pathogenesis.